Of limits and growth : the rise of global sustainable development in the twentieth century - Macekura, Stephen J. (Cambridge : Cambridge University Press, 2015)
Of Limits and Growth connects three of the most important aspects of the twentieth century: decolonization, the rise of environmentalism, and the United States' support for economic development and modernization in the Third World. It links these trends by revealing how environmental NGOs challenged and reformed development approaches of the US government, World Bank, and United Nations from the 1960s through the 1990s. The book shows how NGOs promoted the use of'appropriate' technologies, environmental reviews in the lending process, development plans based on ecological principles, and international cooperation on global issues such as climate change. It also reveals that the'sustainable development' concept emerged from transnational negotiations in which environmentalists accommodated the developmental aspirations of Third World intellectuals and leaders. In sum, Of Limits and Growth offers a new history of sustainability by elucidating the global origins of environmental activism, the ways in which environmental activists challenged development approaches worldwide, and how environmental non-state actors reshaped the United States' and World Bank's development policies.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Sustainable development -- History -- 20th century; Environmental protection; Sustainable development -- Citizen participation; Environmental policy